Research Trend on Digital Financial Services in Developing Countries in the Last Five Years (2020-2024) - Mohamad Arief Rafsanjani; Susanti, Susanti; Surjanti, Jun; Dewi, Retno Mustika; Srisuk, Prattana (International Journal Business, Management and Innovation Review, 2025)
The rapid expansion of digital financial services (DFS) in developing countries presents significant opportunities for financial inclusion, yet the research landscape in this domain remains fragmented and underexplored. This study conducts a bibliometric analysis to examine research trends on digital financial services (DFS) in developing countries over the past five years (2020–2024). Using a dataset of 425 publications sourced from a bibliographic database, the study evaluates scholarly output, citation patterns, and influential contributions. The findings reveal a significant growth in DFS research, with the number of publications increasing from 47 in 2020 to 131 in 2024, reflecting the rising importance of DFS in fostering financial inclusion and economic development. China leads in scholarly output and citation impact, followed by India and South Africa, underscoring the global interest in this domain. Key research themes include financial inclusion, electronic money adoption, and regulatory frameworks, while high-impact topics, such as cryptocurrency and digital currency adoption, highlight emerging areas of interest. The study identifies foundational contributions from 2020 as pivotal in shaping the field and highlights geographic disparities in research output. These findings offer valuable insights for academics, policymakers, and industry practitioners, emphasizing the need for collaborative and multidisciplinary efforts to address barriers to DFS adoption and leverage its potential for economic growth in developing countries.